Analysis Of The Effect Of Company Size, Profitability And Leverage On Corporate Social Responsibility Disclosure - Wiji Muntari; Mariyam Chairunisa (Baca Dulu Publisher, 2024)
This study aims to examine the effect of Company Size, Profitability and Leverage on Disclosure of Corporate Social Responsibility. Corporate social responsibility is an inherent responsibility of every investment company to continue to create relationships that are harmonious, balanced and in accordance with the environment, values, norms and culture of the local community. Disclosure Corporate social responsibility is an organizational responsibility for the impact of all decisions and activities on society and the environment which is manifested in the form of transparent and ethical behavior that is in line with the principles of sustainable development. The population in this study are banking companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period. The sample in this research was 26 out of 46 companies that met the criteria so that the total sample used in this study during the 2017-2020 period was 104 observational data. The research design used was quantitative research and the sampling method used in this study was purposive sampling method. The data used in this research is secondary data. The data analysis method used in this study is multiple linear regression analysis with the help of the SPSS Version 25 application program. The results of the analysis show that (i) company size has a positive and significant effect on corporate social responsibility disclosure, (ii) profitability has a positive and significant effect on disclosure of corporate social responsibility (iii) leverage has a positive and significant effect on disclosure of corporate social responsibility.